Coronary heart disease trends in England and Wales from 1984 to 2004: concealed levelling of mortality rates among young adults. Issue 2 (19th July 2007) - O'Flaherty, M; Ford, E; Allender, S; Scarborough, P; Capewell, S
Abstract : Background: Trends in cardiovascular risk factors among UK adults present a complex picture. Ominous increases in obesity and diabetes among young adults raise concerns about subsequent coronary heart disease (CHD) mortality rates in this group. Objective: To examine recent trends in age-specific mortality rates from CHD, particularly those among younger adults. Methods and results: Mortality data from 1984 to 2004 were used to calculate age-specific mortality rates for British adults aged 35+ years, and joinpoint regression was used to assess changes in trends. Overall, the age-adjusted mortality rate decreased by 54.7% in men and by 48.3% in women. However, among men aged 35–44 years, CHD mortality rates in 2002 increased for the first time in over two decades. Furthermore, the recent declines in CHD mortality rates seem to be slowing in both men and women aged 45–54. Among older adults, however, mortality rates continued to decrease steadily throughout the period. Conclusions: The flattening mortality rates for CHD among younger adults may represent a sentinel event. Deteriorations in medical management of CHD appear implausible. Thus, unfavourable trends in risk factors for CHD, specifically obesity and diabetes, provide the most likely explanation for the observed trends.